The Puzzle of ASEAN Instruments to Combat Human Trafficking - Smerchuar, Numtip; Madhyamapurush, Warach (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
Human trafficking came to the public concern in the 1990s, caused by the movement of people and the operation of organized crime. As the problem grew more complex, collaboration was needed to enhance effective mechanisms to combat human trafficking. However, ASEAN Countries, after more than two decades in fighting against human trafficking issue, efforts in prevention and protection found limited results due to the fluctuating number of trafficked victims in the region. This paper aims to examine the mechanisms and the development of instruments to enhance the efforts in tackling human trafficking problems of ASEAN by employing the descriptive approach of policy analysis, focusing specifically on regional practices and policy development. Data were mainly collected English-based documents; it can be concluded that collaboration among ASEAN countries has been initiated various types of regional instruments. However, the success of practices following the existing regional framework remains murky.